2019
DOI: 10.3390/s19132857
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Label-Free Detection of As3+ using 3-nitro-L-tyrosine as an As3+-chelating Ligand

Abstract: A simple and rapid As3+ detection method using 3-nitro-L-tyrosine (N-Tyr) is reported. We discovered the specific property of N-Tyr, which specifically chelates As3+. The reaction between As3+ and N-Tyr induces a prompt color change to vivid yellow, concomitantly increasing the absorbance at 430 nm. The selectivity for As3+ is confirmed by competitive binding experiments with various metal ions (Hg2+, Pb2+, Cd2+, Cr3+, Mg2+, Ni2+, Cu2+, Fe2+, Ca2+, Zn2+, and Mn2+). Also, the N-Tyr binding site, binding affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…331−335 Recently, 3-nitrotyrosine as a fluorescent biosensor for As 3+ , Cl − and I − ions was also reported. 336,337 Similarly, it has been shown that 2-nitrotyrosine can act as a FRET quencher to Trp and has been used to study the binding structure of prolinerich peptides and SH3 domain from a yeast myosin. 312 In addition, it has been reported that several fluorotyrosines, such as 2-fluorotyrosine and 3-fluorotyrosine, can tune the fluorescence spectrum of GFP, 338,339 and that the fluorescence of 3-fluorotyrosine can be quenched by phosphate.…”
Section: Phenylalanine-based Uaasmentioning
confidence: 99%
See 1 more Smart Citation
“…331−335 Recently, 3-nitrotyrosine as a fluorescent biosensor for As 3+ , Cl − and I − ions was also reported. 336,337 Similarly, it has been shown that 2-nitrotyrosine can act as a FRET quencher to Trp and has been used to study the binding structure of prolinerich peptides and SH3 domain from a yeast myosin. 312 In addition, it has been reported that several fluorotyrosines, such as 2-fluorotyrosine and 3-fluorotyrosine, can tune the fluorescence spectrum of GFP, 338,339 and that the fluorescence of 3-fluorotyrosine can be quenched by phosphate.…”
Section: Phenylalanine-based Uaasmentioning
confidence: 99%
“…However, various Tyr-based UAAs have been shown to be useful as fluorescence quenchers of other biological fluorophores. For example, 3-nitrotyrosine (3NT), which is nonfluorescent, is an efficient quencher of Tyr and Trp fluorescence, because its absorption spectrum is in the wavelength range of 300–450 nm (depending on pH, the λ ab of its neutral form is at 355 nm, whereas the λ ab of its ionized form is at 422 nm) and overlaps with the emission spectra of Tyr and Trp. , The Trp and 3NT fluorophore–quencher pair has an R 0 distance of ca. 26 Å and has been used to study protein folding and structural change, ,, and protein–protein interactions. Recently, 3-nitrotyrosine as a fluorescent biosensor for As 3+ , Cl – and I – ions was also reported. , Similarly, it has been shown that 2-nitrotyrosine can act as a FRET quencher to Trp and has been used to study the binding structure of proline-rich peptides and SH3 domain from a yeast myosin . In addition, it has been reported that several fluorotyrosines, such as 2-fluorotyrosine and 3-fluorotyrosine, can tune the fluorescence spectrum of GFP, , and that the fluorescence of 3-fluorotyrosine can be quenched by phosphate …”
Section: Fluorescence Probesmentioning
confidence: 99%